Novel CRB1 pathogenic variant in Chuuk families with Leber congenital amaurosis. Issue 4 (3rd January 2023) - Albakri, Amani; Pisuchpen, Phattrawan; Capasso, Jenina E.; Schneider, Adele; Kopinsky, Sarina; Glaser, Tom; Chiang, John P.‐W.; Yomai, Anamaria Akapito; McNear, Donna; Levin, Alex V.
Abstract: The purpose of this article is to determine the cause of Leber congenital amaurosis (LCA) in Chuuk state, Federated States of Micronesia (FSM). In this prospective observational case series, five patients with early‐onset vision loss were examined in Chuuk state, FSM, during an ocular genetics visit to study the elevated incidence of microphthalmia. Because of their low vision these patients were incorrectly assumed to have microphthalmia. A complete ophthalmological exam established a clinical diagnosis of LCA. Candidate gene exons were sequenced with a targeted retinal dystrophy panel. Five subjects in three related families were diagnosed with LCA. All five were from Tonoas Island, within the Chuuk Lagoon, with ages ranging from 6 months to 16 years. DNA sequencing of affected individuals revealed a homozygous CRB1 NM_201253.3:c.3134del pathogenic variant, which was heterozygous in their parents. CRB1 genotypes were confirmed by a PCR restriction assay. We report identification of a founder pathogenic variant in CRB1 responsible for autosomal recessive LCA in this isolated community. This discovery will lead to appropriate recurrence risk counseling.